MANAJEMEN KURIKULUM PENDIDIKAN AGAMA ISLAM DI MADRASAH DAN PERGURUAN TINGGI - Saefrudin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
The Islamic Religious Education Curriculum: What Does It Mean? What features distinguish Islamic religious instruction at madrasas, and what part do instructors play in this context? The administration of the Islamic Religious Education Curriculum in Madrasas and Universities is the focus of this study. Methodology for research. The Liberiy Researcher case study type is used in this qualitative research project. Using a literature review approach, this study finds and emphasises pertinent themes and records significant findings, frameworks, and tools from earlier studies that may be used as a foundation for future research. The study's findings demonstrate that attempts to teach the Islamic faith, whose doctrine is founded on the Koran and Hadith, are referred to as Islamic religious education. Characteristics Highlights religious and moral goals. Broadly encompassing and comprehensive in content, namely a curriculum that truly reflects the spirit of thought and comprehensive teachings. The curriculum has undergone several changes. and the latest is the 2013 curriculum or better known as K-13. In the development of the PAI curriculum at PTU.